Deeply cooled and temperature controlled microjets: Liquid ammonia solutions released into vacuum for analysis by photoelectron spectroscopy - Buttersack, Tillmann; Mason, Philip E; Jungwirth, Pavel; Schewe, H Christian; Winter, Bernd; Seidel, Robert; McMullen, Ryan S; Bradforth, Stephen E (The Review of scientific instruments, 2020)
A versatile, temperature controlled apparatus is presented, which generates deeply cooled liquid microjets of condensed gases, expelling them via a small aperture into vacuum for use in photoelectron spectroscopy (PES). The functionality of the design is demonstrated by temperature- and concentration-dependent PES measurements of liquid ammonia and solutions of KI and NH4I in liquid ammonia. The experimental setup is not limited to the usage of liquid ammonia solutions solely.